2017
DOI: 10.3389/fpls.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Modulating AtDREB1C Expression Improves Drought Tolerance in Salvia miltiorrhiza

Abstract: Dehydration responsive element binding proteins are transcription factors of the plant-specific AP2 family, many of which contribute to abiotic stress responses in several plant species. We investigated the possibility of increasing drought tolerance in the traditional Chinese medicinal herb, Salvia miltiorrhiza, through modulating the transcriptional regulation of AtDREB1C in transgenic plants under the control of a constitutive (35S) or drought-inducible (RD29A) promoter. AtDREB1C transgenic S. miltiorrhiza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Overexpression of the ZmGOLS2 gene enhanced plant abiotic stress tolerance under stress conditions, and did not cause a growth penalty under normal growth conditions (Gu et al ., ). Circumventing a growth penalty has been possible through the inducible expression of transcription factor genes, such as DREB s, controlled by the RD29 promoter, and this has enhanced plant tolerance of drought stress with minimal effects on plant growth (Kasuga et al ., ; Wei et al ., , ). Nevertheless, considering that the endogenous DREB s are also induced by drought stress through the activation of their own promoter, and the plants are still sensitive to drought stress, the inducible expression of a transcription factor gene has to be precisely controlled temporally and to the correct degree to enhance plant abiotic stress tolerance without causing growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the ZmGOLS2 gene enhanced plant abiotic stress tolerance under stress conditions, and did not cause a growth penalty under normal growth conditions (Gu et al ., ). Circumventing a growth penalty has been possible through the inducible expression of transcription factor genes, such as DREB s, controlled by the RD29 promoter, and this has enhanced plant tolerance of drought stress with minimal effects on plant growth (Kasuga et al ., ; Wei et al ., , ). Nevertheless, considering that the endogenous DREB s are also induced by drought stress through the activation of their own promoter, and the plants are still sensitive to drought stress, the inducible expression of a transcription factor gene has to be precisely controlled temporally and to the correct degree to enhance plant abiotic stress tolerance without causing growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Such genes include AUX/IAA , GH3 , and SAUR . Auxin biosynthesis is known to confer drought tolerance in Rice [ 35 ], OsGH3-2 a member of the GH3 family was proved to be modulating the level of ABA and stress tolerance in rice [ 36 ], SAUR genes has not been yet functionally characterized, are altered by auxin and are hypothesized to be involved in the drought tolerance by auxin [ 37 ]. GID1 and Phytochrome interacting factor 4 are involved GA signaling and in regulating drought stress responses [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCR procedure went as follows: at 95°C for 30 s, then 40 cycles of 95°C for 5 s and 60°C for 30 s, this program was followed by a melting curve analysis (65–95°C with temperature increment of 0.5°C every 5 s). In this study, the qRT-PCR data for the genes responding to the ABA treatment were normalized to β -actin ( Yang et al, 2012 ; Wei et al, 2017 ), while the other qRT-PCR data were normalized to β -actin and ubiquitin ( Yang et al, 2010 ; Xiao et al, 2011 ). All the primers used for the qRT-PCR analysis are listed in Supplementary Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“…Because their quality and quantity strongly depends on environmental stresses, such as drought, cold, and salinity, this results in a lower yield of S. miltiorrhiza ( Akula, 2011 ; Liu et al, 2011 ; Zhao et al, 2014 ). Several studies have reported that by overexpressing SmLEA2 , AtDREB1A , AtDREB1B , and AtDREB1C , the salt and drought tolerance of transgenic S. miltiorrhiza was improved ( Wei et al, 2016a , b , 2017 ; Wang et al, 2017 ). More of such genes should be investigated via genetic engineering methods, as it could assist in breeding new varieties of S. miltiorrhiza that have a higher content of active ingredients and a stronger tolerance to stresses.…”
Section: Introductionmentioning
confidence: 99%